Management of Swanggi Fish (Priacanthus Macracanthus) in the Waters of the Port of Nusantara Fishery Port Ratu - Dewi, Kadek Pritha; Susiloningtyas, Dewi; Budiharsono, Sugeng (International Journal of Educational Research Excellence (IJERE), 2024)
Indonesia has two-thirds of its territory covered by sea, making it rich in marine resources, especially fish. According to the Census of Marine Life, there are around 950 thousand species that inhabit the world's oceans, but only about one percent have been exploited. In Indonesia itself, FishBase records around 4743 types of fish, making it the country with the largest Marine Mega-Biodiversity in the world (Jabbar, 2018). There are two main problems in the fisheries sector in Indonesia: economics and biology. Biological problems include threats to the sustainability of fish stocks, while economic problems are related to the lack of profits obtained by fishermen from catches and sustainable use of fish resources (Akoit and Nalle, 2018). The Archipelago Fisheries Port (PPN) plays an important role in supporting fishing activities in the Indian Ocean, including in Palabuhanratu, West Java. Palabuhanratu is an important location for landing various types of fish, especially large pelagic fish such as tuna and skipjack, as well as swanggi fish (Priacanthusmacracanthus), which experienced a significant increase in production from 573 tonnes in 2013 to 18,730 tonnes in 2015 (Sadewi et al., 2018). Swanggi fish is a demersal fish with high economic value that is in demand by the public and is an export commodity to Korea, Japan and China. However, high demand results in overfishing and a decline in adult fish stocks (Jabbar et al., 2017). This research is descriptive quantitative research which aims to measure the level of variables through samples. The analytical methods used include analysis of biological aspects of swanggifish, catch analysis methods, and sustainability analysis methods using Rapid Appraisal for Fisheries (RAPFISH). It is hoped that the results of this research can provide a sustainable shrimp resource management strategy based on the data obtained.